World Development Indicators 2000 - World Bank; World Bank (Washington : The International Bank for Recontsruction and Development / The World Bank, 2000)
This CD-ROM contains a database of more than 500 timeseries indicators covering the years 1960 through 1998, where data are available. It is also contains all the tables from the World Development Indicarors book and the Atlas, including those covering the 200 or so indicators for which only a single year of data is available
System requirements:Windows, Microsoft Excel, Microsoft Access, dBase, SAS
Keywords: Economic history -- 1945; Economic indicators; Economic development